2020
DOI: 10.1093/conphys/coaa085
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of parasitism and stress physiology in wild giant pandas

Abstract: Many factors, including the inner status of the individuals and external environment, can influence the parasite infections and stress physiology in mammals. Here, we explored the influence of the sex, age, reproductive season and seasonal food availability on the parasitism and stress physiology in wild giant pandas (Ailuropoda melanoleuca) through nutrient and steroid hormone analysis and parasitic infection measurement. Diet composition had significant influences on the faecal cortisol levels and parasite l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This study confirms that higher parasite loads in the giant pandas increase their FGM level. Meanwhile, sex and reproductive season have no significant correlation with cortisol level of the studied giant pandas (Zhou et al, 2020).…”
Section: 4mentioning
confidence: 80%
See 2 more Smart Citations
“…This study confirms that higher parasite loads in the giant pandas increase their FGM level. Meanwhile, sex and reproductive season have no significant correlation with cortisol level of the studied giant pandas (Zhou et al, 2020).…”
Section: 4mentioning
confidence: 80%
“…The study aims to study the effect of sex, age, reproductive season and seasonal food availability on the parasitism and the level of stress of wild giant pandas. FGM analysis through RIA shows that parasite prevalence increased during bamboo shoot Zhou et. al., (2020) The study was conducted to monitor the FGM level between parturient and non-parturient female panda that lives in Smithsonian National Zoological Park and Zoo Atlanta through EIA.…”
Section: Melursus Ursinusmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing non-invasive tools to monitor giant panda sex steroids and how these interact with the stress-related hormone cortisol is important not only for breeding programs and the welfare of captive giant pandas ( Yu et al. , 2011 ) but also as a means to assess the performance of strategies designed to reduce disturbances in wild panda populations ( Zhou et al. , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why cats with high stress scores are more likely to develop upper respiratory infection [17,19,20], which is highly prevalent in shelter cats [21]. The correlation between stress physiology and parasite infection has been widely reported in wildlife [22,23] and it has been suggested that the persistence of parasites in the host without inducing chronic stress responses supports the hypothesis that the hosts are tolerant to their parasites [24]. However, a study on dogs housed in an animal shelter revealed that, although it was suspected that shedding parasite ova would be impacted by the stressors associated with shelter housing, the plasma cortisol concentration decreased with time, whereas parasite shedding was unaffected by the duration of the shelter stay [25].…”
Section: Introductionmentioning
confidence: 99%